Cemetery in Posada Rybotycka, voivodeship Przemysl - Piontek, Janusz; Malinowski, Andrzej (Anthropological Review, 1976)
The paper presents the anthropological analysis of skeletal material originating from 17th-18th centuries A.D. uncovered close to an orthodox church in Posada Rybotycka. Biological state of investigated group has been rescribed on the grounds of life table functions (tab. 1). Juvenile (individuals were not taken into consideration when computing life tables since their numbers were too scarce in relation to adults. Individual measurements of the skulls are given in table 2 whereas parametres of their distributions are listed in table 3. Individuals belonging to examined group had, at average, short braincases, broad upper faces, broad noses and orbits of medium height. Average stature was 167.2 cm for males (N=15) and 158.6 cm for females (N=23), Frequency of dental caries reached 28.4% in 72% of individuals were found carious teeth, there were no observed tooth anomalies in the sample. Differences between the population of Posada Rybotycka and other groups from Poland and Czechoslovakia were assesed by comparing standarized differences in cranial measurements. There were found significant differences in length and breadth of braincase between examined population and populations from Ostrów Lednicki, Gródek and Wiślica. The smallest differences were present between Posada Rybotycka group and the others in such characters as frontal breadth, dimensions of orbits, nasal breadth and height of braincase. In order to obtain a multivariative measure of distances between populations Penrose’s general, shape and size distances were calculated.